2007
DOI: 10.1515/znb-2007-1008
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Carboxylate Anions on a CaCO3 Surface

Abstract: The adsorption behavior of benzoate, citrate, tartrate and glutamate on calcite dispersed in water was studied. At r. t. and pH = 9, the molar amount of substrate adsorbed decreases with increasing number of carboxylic groups in the molecule. Thus, monofunctional benzoate adsorbs in significantly higher molar amounts than trifunctional citrate. A more alkaline environment (pH = 12.5) has almost no effect on the adsorption behavior whereas a temperature increase, particularly from 40 to 60 • C, results in notab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 18 publications
3
25
0
2
Order By: Relevance
“…Generally, effective dispersion of aqueous suspensions prepared from inorganic particles is achieved either by electrostatic repulsion between the particles loaded with adsorbed polyelectrolyte, or by a steric effect provided by comb‐shaped polymers possessing graft chains . So far, very few experimental data on the driving forces behind the adsorption process of cement superplasticizers are available.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, effective dispersion of aqueous suspensions prepared from inorganic particles is achieved either by electrostatic repulsion between the particles loaded with adsorbed polyelectrolyte, or by a steric effect provided by comb‐shaped polymers possessing graft chains . So far, very few experimental data on the driving forces behind the adsorption process of cement superplasticizers are available.…”
Section: Introductionmentioning
confidence: 99%
“…This explains the effectiveness of R2 over R1 as can been seen in Figures 3 and 4 great effect on the retardation process, which can be considered as one of many criteria for better retarder quality (Bassioni, 2012). This is attributable to the competition between the inorganic salts for the positive adsorption sites on the hydration products, especially ettringite, which causes the effectiveness of R1 to be reduced (Bassioni, 2010;Plank and Bassioni, 2007). The origin of the carbonate ions can be attributed to the industrial synthesising process.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, wettability of limestone for all asphaltenic solutions except 5 wt% is believed to follow this mechanism. According to a study conducted by Plank and Bassioni [37], CaCO 3 was found to correspond to a Type II isotherm [38].…”
Section: Wettability Alteration Due To Asphaltenementioning
confidence: 97%